A novel core-shell structured poly-m-phenyleneisophthalamide@polyvinylidene fluoride nanofiber membrane for lithium ion batteries with high-safety and stable electrochemical performance. (20th March 2019) - Wang, Liyuan; Deng, Nanping; Ju, Jingge; Wang, Gang; Cheng, Bowen; Kang, Weimin
Abstract: In this study, a novel core-shell structured poly-m-phenyleneisophthalamide@polyvinylidene fluoride (PMIA@PVDF) nanofiber separator was successfully synthesized via facile coaxial electrospinning. The thermal resistance, electrolyte uptake, ion conductivity as well as anodic stability window of the nanofiber separator were synchronously improved to above 260 °C, 753%, 1.7 mS cm −1 and 5.0 V, which resulted in an appealing safety and electrochemical performance. The markedly enhanced performance could be ascribed to the synergistic advantages of the PMIA core and PVDF shell in the homogeneous PMIA@PVDF nanofiber separator. The PMIA core in PMIA@PVDF nanofiber with high melting point and rigidity character acting as stable skeleton strengthened the thermal stability and integrity of the whole separator. Meanwhile, the lyophilic PVDF shell along with the interconnected open pore structure of electrospinning membrane guaranteed the membrane wettability to electrolyte so as to the ion conduction. Most impressively, under high temperature treatments above 180 °C, the PVDF shell could melt and completely occlude the macropores in PMIA@PVDF nanofiber separator to shut down the battery operation without obvious dimensional shrinkage. Thus, the superiorities in electrochemical performance and safety made PMIA@PVDF nanofiber separator a highly qualified separator for high performance lithium ion battery. Graphical abstract: Image 1